Treatment of intra‐anal warts with imiquimod 5% cream: A single‐center prospective open study. Issue 4 (18th January 2021) - Irisawa, Ryokichi; Tsuboi, Ryoji; Saito, Masuyoshi; Harada, Kazutoshi
Abstract: Intra‐anal warts are frequently recalcitrant to surgical removal, but imiquimod 5% cream is not formulated to use in clinical practice due to the risk of mucosal inflammation. In the present, prospective, open study examining the efficacy and safety of imiquimod 5% cream, the drug was applied to the entire inner surface of the anal canal with a cotton swab under anoscopy three times weekly for 16 weeks. If complete remission was not achieved, the treatment was continued until week 28. Electrocautery was applied once in a poorly responsive case. In total, 21 patients with intra‐anal warts, of whom 16 were HIV‐positive, were enrolled. Two patients withdrew before week 16, and nine more patients withdrew before week 28. The complete clearance rate was 36.8% (7/19) at week 16 and 70% (7/10) at week 28. Four patients achieved complete clearance at week 16 and maintained clearance at week 28 without further treatment. Three of four patients resistant to previous electrocautery achieved clearance with imiquimod 5% cream treatment. Adverse events occurred in 81% (17/21) of the patients mainly at the application site, but serious or previously unencountered adverse events were not observed. Imiquimod 5% cream applied to intra‐anal warts was nearly as efficacious and safe as when applied to external anogenital warts. Since treatment modalities for intra‐anal warts are very limited, application of imiquimod 5% cream alone with careful and frequent observation or in combination with electrocautery is a useful option for refractory cases of intra‐anal wart.